(untitled) (Experimental biology, 2024)
This work explores the role of Ca2+ in the regulation of epileptiform activity of neurons. The research was carried out on a unique setup that allows simultaneous recording of neuron electrical activity and measurement of calcium ion concentration changes by optical method. The uncovering of the mechanisms of Ca2+ ions influence on the parameters of epileptiform activity is an important step in the control of this complex process and opens new ways of pharmacological correction of hyperexcitation. The aim of this study was to investigate the role of Ca2+ ions in the regulation of epileptiform neuronal activity. The result of the research with the use of intracellular calcium buffer BAPTA established the dependence of the amplitude of slow depolarisation, the duration of the paroxysmal depolarisation shift cluster and the amplitude of action potentials of different types of neurons on the concentration of Ca2+ ions in the cytoplasm. Decreasing the amplitude of Ca2+ pulses during epileptiform activity while accumulating intracellular Ca2+ buffer has different effects on different types of neurons. A decrease in cluster amplitude occurs in the GABAergic neuron without a change in the duration of the action potential burst, while in the glutamatergic neuron the duration of the cluster decreases without a change in amplitude. The depolarising pulse of the cluster in the first case is independent of Ca2+ concentration, while in the second case it is due to a Ca2+-dependent process (opening of a Ca2+-dependent depolarising channel). Thus, this work shows for the first time different mechanisms of action of intracellular fast Ca2+ buffer in glutamatergic and GABAergic neurons, which is an important step in understanding Ca2+-dependent mechanisms of regulation of epileptic brain activity.